BLNK mutation associated with T-cell LGL leukemia and autoimmune diseases: Case report in hematology - Fouquet, Guillemette; Rossignol, Julien; Ricard, Laure; Guillem, Flavia; Couronné, Lucile; Asnafi, Vahid; Vavasseur, Manon; Parisot, Mélanie; Garcelon, Nicolas; Rieux-Laucat, Frédéric; Mekinian, Arsène; Hermine, Olivier (Frontiers in Medicine, 2022)
We present the case of a female patient with a heterozygous somatic BLNK mutation, a T-cell LGL (large granular lymphocyte) leukemia, and multiple autoimmune diseases. Although this mutation seems uncommon especially in this kind of clinical observation, it could represent a new mechanism for autoimmune diseases associated with LGL leukemia. The patient developed several autoimmune diseases: pure red blood cell apalsia, thyroiditis, oophoritis, and alopecia areata. She also presented a T-cell LGL leukemia which required treatment with corticosteroids and cyclophosphamide, with good efficacy. Interestingly, she had no notable infectious history. The erythroblastopenia also resolved, the alopecia evolves by flare-ups, and the patient is still under hormonal supplementation for thyroiditis and oophoritis. We wanted to try to understand the unusual clinical picture presented by this patient. We therefore performed whole-genome sequencing, identifying a heterozygous somatic BLNK mutation. Her total gamma globulin level was slightly decreased. Regarding the lymphocyte subpopulations, she presented a B-cell deficiency with increased autoreactive B-cells and a CD4+ and Treg deficiency. This B-cell deficiency persisted after complete remission of erythroblastopenia and LGL leukemia. We propose that the persistent B-cell deficiency linked to the BLNK mutation can explain her clinical phenotype.